The consumer value proposition for a hypothetical Digital Canadian Dollar - Martine Warren; Bill Laur; Ted Garanzotis; Sebastian Hernandez (Bank of Canada, 2024)
Research into a hypothetical Digital Canadian Dollar has largely focused on public policy, financial technology innovations and public opinion. In this study, we explore the consumer value proposition of a hypothetical Digital Canadian Dollar, considerations for its adoption and the users who would benefit most from this potential new payment method. We employ a design-thinking consultation methodology, allowing participants to interact with research prototypes of increasing complexity to reveal user preferences, constraints, and adoption influences. Qualitative insights are corroborated using quantitative, large-population surveys and contrasted with results from a Bank of Canada open online public consultation. We find that most participants would support the issuance of a hypothetical Digital Canadian Dollar, and we identify the segments most likely to be early adopters. However, broad early adoption is unlikely given that available payment methods meet the needs of most users. Financially vulnerable segments often have the most to gain from this new payment method but are most resistant to adoption. Important considerations for appeal and adoption potential include universal merchant acceptance, low costs, easy access, simplified online payments, shared payment features, budgeting tools, and customizable security and privacy settings. Participants cited these features far more often than offline functionality and the ability to make anonymous payments. Our results also show that cash remains an important method of payment and that certain groups may strongly resist a Digital Dollar if they conflate its launch with the end of cash issuance. We find a hypothetical Digital Canadian Dollar requires the support of an information campaign to be understood, valued and adopted.
Keywords: C9; D12; E42; E58; O3; O33; 330; Accessibility; Bank notes; Central bank research; Digital currencies and fintech